Psychological, Social, Cultural, Literary and Legal Dimensions of Memory - Sadowski, Mirosław Michał (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
As many researchers have pointed out, the past two decades have seen ‘a hypertrophy of memory’. Never before have so many different disciplines investigated the mysteries behind the ways we remember, trying to show that memory does influence various sciences, from sociology, to law, to literature. This article ventures to outline the scope of these investigations, looking at memory from a different, broad perspective. Following a short introduction, section two focuses on the ‘technical’ details of memory, explaining how our mind remembers (and forgets), and remarking upon the so-called ‘sins of memory’. Section article addresses social aspects of memory, in particular the notion of collective memory. The author explains this increasingly popular term, introducing several other interconnected expressions. Section four focuses on cultural dimensions of memory. It first outlines, then analyses the relationship memory and philosophy have had through the ages, showing how the perceptions of the latter have changed. Next, the author evokes the once popular, nowadays slightly forgotten discipline, known as mnemotechnics, or ‘art of memory’. Section five is devoted to the relations between literature and memory. The article first explains how, in many ways, memory influences literature and then argues that literature is one of the best grounds to observe how different mechanisms of memory work. Thus, the author analyses three contemporary works, Marcel Proust’s In the Search of Lost Time, Jarosław Iwaszkiewicz’s Maidens of Wilko, and Czesław Miłosz’s Lost Places, showing how they can help us unveil some of memory’s mysteries. In the last part of the essay, the author investigates the ties between international law and collective memory. Giving insight into this unobvious relationship, on the examples of present-day Argentina and Germany, the article notes that international law both influences and is influenced by collective memory.
Keywords: pamięć; hipertrofia pamięci; sztuka pamięci; mnemotechnika